PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA AUDIOVISUAL TERHADAP KETERLIBATAN IBU DALAM PROSES INISIASI MENYUSU DINI DI PUSKESMAS JETIS YOGYAKARTA - , SETTAVIANTI JIHAD W ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Mother knowledge of Early Breastfeeding Initiation is one of the important factors affecting mother involvement to increase success in the implementation of Early Breastfeeding Initiation. It required exposure to media information interesting that maternal knowledge about Early Breastfeeding Initiation in order to be implemented properly and adequately. Objective: To determine the effect of health education with audiovisual media against the mother's involvement in the process of Early Breastfeeding Initiation and knowing mean difference scores maternal involvement and successful implementation of Early Breastfeeding Initiation in the group given health education with audiovisual media and without any given health education with audiovisual media in Jetis health center, Yogyakarta. Methods: This study used a quantitative research method and design of quasi-experimental posttest-only control design. The study was conducted in March until Mei 2014 with research subjects were 28 respondents. Data were collected by observation when carried out the Early Breastfeeding Initiation after given intervention. Results: The mean score of maternal involvement in the process of Early Breastfeeding Initiation by 7.93 in the control group and the intervention group in the amount of 12.43. P-value = 0.00, since p <0.05. Based on the difference in value is known that the p value is obtained for p = 0.00 (p <0.05) which means that the effect obtained following an intervention. Conclusion: There is the effect of health education with audiovisual media to the mother's involvement in the process of Early Breastfeeding Initiation in Puskesmas Jetis Yogyakarta